A Critical Reflection of Ethical Issues in Research - McNeill, Hinematau (Te Kaharoa, 2008)
This article uses the concept of matauranga as a starting point as a device for exploring concepts of Maori mental wellness. Issues of the role of culture are explored in depth, both from theoretical and application perspectives. The iwi of Tuhoe are the focus of attention in the examination of these themes.